The expression of the nth term can be written using the formulas
A. nth term =

B. nth term =
.
The expression of the nth term can be written as:
For the sequence 4, 1, -2, -5, -8............................
the first term a = 4 and the common difference d = -3.
aₙ =

aₙ =

Therefore, the nth term is given by the formula aₙ =
.
For the sequence -7, -12, -17, -22, -27...................
the first term a = 7 and the common difference d = -5.
aₙ =

aₙ =

Therefore, the nth term is given by the formula aₙ =
.